Potential and Agricultural Development Strategies in Cupak Village, Ngusikan District, Jombang Regency - Wardah Wardah; Angga Dutahatmaja (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of the research is to find out and dig deeper into the potential of agriculture to design a development strategy for the potential of agriculture in Cupak village. Design/methodology/approach: The research method is descriptive analytic which is carried out randomly at the Cupak Village Farmers Group. Samples were taken as many as 150 farmers who own land and cultivators. Data analysis was carried out descriptively and SWOT. The results of the analysis show that: 1) Agricultural potential in Cupak Village includes: a) active human resources in farmer group activities, b) producers of food crops, secondary crops, horticulture and plantations with the main plantation food commodities being porang and gadung, c) agricultural land quite fertile, d) small risk of pest disorders. 2) Agricultural development strategies that can be applied include: a) Development of agricultural products to increase product selling value, b) Empowerment of institutions and farmer organizations, c) Revitalization of technological innovation, and d) Development of access to distribution networks and product marketing. Findings: Based on the results of the SWOT analysis, it shows that the strength of Cupak Village in the development of agriculture is quite good, because the conditions in developing agriculture in Cupak Village are very supportive. The condition of the area is very potential for the development of tuber farming, especially Porang and Gadung. The number of farmers is quite large, both owner farmers and farm laborers, and the need for fertilizers and other inputs is also available. The majority of the people's livelihood in the village is as farmers and ranchers. Root crops also do not require intensive care so that they are suitable to be developed as a mainstay agriculture in Cupak Village. Livestock, especially ruminants such as cattle and goats/sheep, have a large population and are a slow source of income for the farmers of Cupak Village. Research limitations/implications: This study discusses how to increase the potential and development of agricultural strategies in Cupak Village, Jombang. Practical implications: The results of this study, the agricultural potential of Cupak Village, Jombang can develop and can improve the standard of living of farmers in Cupak Village, Jombang. Originality/value: Potential and strategies for agricultural development in Cupak Village, Jombang with direct surveys to farmers in Cupak Village, Jombang. Paper type: Research paper